Influence of Angiotensin II Subtype 2 Receptor (AT2R) Antagonist, PD123319, on Cardiovascular Remodelling of Aged Spontaneously Hypertensive Rats during Chronic Angiotensin II Subtype 1 Receptor (AT1R) Blockade - Emma S. Jones; M. Jane Black; Robert E. Widdop (International Journal of Hypertension)
Cardiac AT2R expression is upregulated in the normal process of aging. In this study we determined the contribution of AT2R to chronic antihypertensive and remodelling effects of AT1R blockade in aged hypertensive rats. Adult (20 weeks) and senescent (20 months) spontaneously hypertensive rats (SHRs) were treated with either the AT1R antagonist, candesartan cilexetil (2 mg/kg/day), the AT2R antagonist, PD123319 (10 mg/kg/day), or a combination of the 2 compounds. Mean arterial pressure (MAP) and left ventricular volume were markedly decreased by candesartan cilexetil, however, simultaneous treatment with PD123319 had no additional effect on either parameter. Perivascular fibrosis was significantly reduced by candesartan cilexetil in aged animals only, and this effect was reversed by concomitant PD123319 administration. Vascular hypertrophy was reduced by candesartan cilexetil, and these effects were reversed by simultaneous PD123319. These results suggest that AT2R stimulation does not significantly influence the antihypertensive effect of chronic AT1R blockade, but plays a role in the regulation of vascular structure. The severe degree of cardiac perivascular fibrosis in senescent animals was regressed by AT1R blockade and this effect was reversed by simultaneous AT2R inhibition, demonstrating an antifibrotic role of AT2R stimulation in the aging hypertensive heart.